Impacto das práticas obstétricas na consecução do papel materno - Ragazzo, Monize Secomandi Mestriner (2021)
Considering obstetric practices and the experience that thousands of women have experienced of violation of their rights and abuse and ill-treatment during pregnancy, childbirth and postpartum, measures to evaluate the care received by women become necessary to contribute to the healthy development of children, women and families. To understand the experiences of women in childbirth and postpartum and their associations in maternal role attainment. This is a quantitative-qualitative, exploratory and descriptive study, based on two steps, application of the Mother-Baby Friendly Birthing Facilities (MBFBF) Thermometer and semi-structured interview with women in the first stage. The data collected in the first stage (quantitative) were obtained through a convenience sample and analyzed descriptively; while in the second stage (qualitative), the data were interpreted by content analysis in the thematic modality addressed by Bardin. The results of the first stage reveal that the women assisted in the institution related to the study are not free of harm. The statements of the women obtained in the second stage of the study resulted in the construction of three thematic categories: 1. "Previous knowledge: power to give birth and care", 2. "Professional posture and becoming a mother" and 3. "Importance of the support network and the pandemic in maternal role attainment ". The experience of women is surrounded by intense feelings, from tension and fear to complete satisfaction and the joy experienced in a unique and transformative moment, which they report with great richness of detail through a look at the posture of each professional who assists them, as a way of facilitating this transition to motherhood. The data obtained through the MBFBF Thermometer and excerpts from the speeches of these women also reinforce the urgent need for evidence-based obstetric practices, health education, the professional and social support network and the alignment between reference services as a way to promote safety for new families, harm reduction and to support participatory parental style and maternal self-efficacy.